1979
DOI: 10.1111/j.1600-0536.1979.tb04834.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed irritation: Hexanediol diacrylate and butanediol diacrylate

Abstract: Ephemeral topical contact with hexanediol diacrylate and butanediol diacrylate may cause delayed irritant dermatitis. During 4 years' observation of 20 workers utilizing these substances in the electron beam coating department of a door factory, contact sensitization did not occur. The characteristics of delayed contact irritancy are enumerated. The disease must be distinguished from allergic contact dermatitis, acute irritant dermatitis and cumulative irritant dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 7 publications
0
21
2
Order By: Relevance
“…However, nasal obstruction and hypersecretion as well as an increased incidence of common colds has been reported in wood furniture workers [Ruppe, 1973;Wilhelmsson and Drettner, 19841. These symptoms seem to correlate with wood dust concentration [Andersen et al, 19771. Inflammation, skin irritation, and allergic contact dermatitis from exposure to acrylates are, potentially, the most likely health effects to workers [Bjorkner et al, 1980;Emmet, 1977;Malten, 1979;Malten et al, 1979;Nethercott, 1981;Nethercott et al, 1983;Whittington, 19811. However, no studies have been published, to our knowledge, on health complaints and/or pathophysiology in upper airways in workers exposed to multifunctional acrylates.…”
Section: Discussionmentioning
confidence: 99%
“…However, nasal obstruction and hypersecretion as well as an increased incidence of common colds has been reported in wood furniture workers [Ruppe, 1973;Wilhelmsson and Drettner, 19841. These symptoms seem to correlate with wood dust concentration [Andersen et al, 19771. Inflammation, skin irritation, and allergic contact dermatitis from exposure to acrylates are, potentially, the most likely health effects to workers [Bjorkner et al, 1980;Emmet, 1977;Malten, 1979;Malten et al, 1979;Nethercott, 1981;Nethercott et al, 1983;Whittington, 19811. However, no studies have been published, to our knowledge, on health complaints and/or pathophysiology in upper airways in workers exposed to multifunctional acrylates.…”
Section: Discussionmentioning
confidence: 99%
“…This started with the identification of this pattern of irritation in the 1970s by Malten. He studied the symptoms of occupational workers exposed to a variety of chemicals that led to a number of similar symptoms that seemed to indicate allergic contact dermatitis, but yet were not sensitized [50,51]. Malten also was the first to use instrumental measurements for water loss and skin impedance to characterize skin damaged by cumulative irritation [52].…”
Section: Methodsmentioning
confidence: 99%
“…He found that occupational contact of the workers to hexanediol diacrylate and butanediol diacrylate resulted in delayed irritant dermatitis as exhibited by a different clinical picture than contact sensitization [50]. This discrimination was the first recorded to demonstrate the importance to clinicians who can be misled in initial identification of irritant dermatitis as allergic contact dermatitis.…”
Section: Clinical Aspectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Irritant reactions generally decrease in intensity after removal of the patch but late maximal inflammation can be seen (13,14). Reproducible reactions are generally allergic in nature, while irreproducible reactions are more likely to be irritant, as demonstrated by Kligman & Basketter (12).…”
Section: Irritancy and "False-positive" Reactionsmentioning
confidence: 99%